2018
DOI: 10.1038/s41416-018-0263-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting peroxiredoxin 1 impairs growth of breast cancer cells and potently sensitises these cells to prooxidant agents

Abstract: Background Our previous work has shown peroxiredoxin-1 (PRDX1), one of major antioxidant enzymes, to be a biomarker in human breast cancer. Hereby, we further investigate the role of PRDX1, compared to its close homolog PRDX2, in mammary malignant cells. Methods CRISPR/Cas9- or RNAi-based methods were used for genetic targeting PRDX1/2. Cell growth was assessed by crystal violet, EdU incorporation or colony formation assays. In vivo growth was assessed by a xenotranspla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 42 publications
(59 reference statements)
2
38
0
Order By: Relevance
“…The cytotoxicity of the prooxidant compounds was assessed as described previously [29]. Briefly, cells were treated with increasing concentrations of Men, Asc, or Men/Asc combination, AUR alone, or combined with either Men or Asc for 24 h. Next, the crystal violet assay was applied to determine the viability of cultured cells [29].…”
Section: In Vitro Combinations With Prooxidant Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cytotoxicity of the prooxidant compounds was assessed as described previously [29]. Briefly, cells were treated with increasing concentrations of Men, Asc, or Men/Asc combination, AUR alone, or combined with either Men or Asc for 24 h. Next, the crystal violet assay was applied to determine the viability of cultured cells [29].…”
Section: In Vitro Combinations With Prooxidant Agentsmentioning
confidence: 99%
“…The cytotoxicity of the prooxidant compounds was assessed as described previously [29]. Briefly, cells were treated with increasing concentrations of Men, Asc, or Men/Asc combination, AUR alone, or combined with either Men or Asc for 24 h. Next, the crystal violet assay was applied to determine the viability of cultured cells [29]. Drug combination studies and their synergy quantification were calculated using the Chou-Talalay method by CompuSyn software v1.0 (Combosyn, Inc., Paramus, NJ, USA) [30] as described previously [9].…”
Section: In Vitro Combinations With Prooxidant Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is, however, clearly overexpressed in breast cancer tissue relative to normal tissue [70]. Recently, Bajor et al demonstrated that PRDX1 is involved in reducing exogenous oxidative stress and induces cell growth in breast cancer [71]. The H2B1 (Histone H2B type 1-C/3/F/G/I) proteins are related to epigenetic regulation.…”
Section: Breast Cancermentioning
confidence: 99%